SAT0163 Systematic switch from innovator infliximab to biosimilar infliximab in inflammatory rheumatic diseases in daily clinical practice: the experience of cochin hospital, paris, france. (15th June 2017) - Avouac, J; Molto, A; Abitbol, V; Salcion, A; Gutermann, L; Conort, O; Chast, F; Jeunne, C Le; Goulvestre, C; Chaussade, S; Kahan, A; Roux, C; et al.
Abstract : Background: Biosimilars of originator biologic therapeutics are going to change medical practices. In October 2015, the medical community of Cochin Hospital decided to systematically propose the switch from innovator infliximab to biosimilar infliximab to all treated patients. Objectives: To investigate efficacy and safety of switching treatment from innovator infliximab to biosimilar infliximab. Methods: This is a usual care study conducted in patients aged >18 years who agreed to switch to biosimilar infliximab, and who received at least 3 infusions of innovator infliximab prior to the switch. The primary outcome of the study was the retention rate of biosimilar infliximab at the time of the third infusion. Secondary outcomes included the factors associated with biosimilar discontinuation, the change between baseline and the last visit (July 2016) in DAS28-CRP (rheumatoid arthritis, RA), BASDAI/ASDAS (axial spondyloarthritis, axSPA) and infliximab trough levels, and the occurrence of adverse events. Results: 260 patients fulfilled the inclusion criteria: 182 patients followed-up in Rheumatology (131 with axSPA, 31 with RA, and 20 with other inflammatory rheumatic diseases), 64 in Gastroenterology and 14 in Internal Medicine. The retention rate at the time of the third biosimilar infusion was 82% (149/182 patients), which was lower than the rate observed in patients with inflammatory bowel diseases or uveitis followed-up in Gastroenterology and Internal Medicine, respectively (71/78 patients, 91%). Between baseline and the last visit (mean follow-up: 34±4.5 weeks), 48/182 (26%) patients, including 36 patients with axSPA, discontinued biosimilar infliximab, mainly due to experienced inefficacy (n=47). No clinical or biological factors were associated with biosimilar discontinuation. One infusion reaction led to treatment discontinuation. No serious adverse events occurred. 43 patients restarted innovator infliximab, 2 patients switched to etanercept, 1 to abatacept and 2 maintained biological-free. In RA patients, the mean DAS28-CRP remained stable from baseline to the last visit: 3.38±1.16 to 3.08±1.08 (p=0.217). In axSpA patients, the mean BASDAI increased from 2.94±2.20 to 3.18±2.21 (p=0.046) and the mean ASDAS increased from 1.79±0.90 to 1.99±1.08 (p=0.022). In RA and axSPA, mean CRP levels at baseline (5.95±6.06 and 5.98±11.14 mg/l respectively) and the last visit (6.52±11.32 and 5.03±8.26 mg/l respectively) were not statistically different (p=0.289 and p=0.271, respectively). Mean infliximab trough levels were similar in patients with RA (3.70±5.36 vs. 3.21±4.35 μg/ml, p=0.551) and AxSPA (5.88±5.82 vs. 5.70±5.42 μg/ml, p=0.617) during follow-up. Conclusions: In the majority of patients, innovator infliximab can be switched to biosimilar infliximab without changes in efficacy and safety during 34 weeks follow-up. However, 26% of patients discontinued biosimilar infliximab, mainly those with AxSPA due to a subjective increase in BASDAI or ASDAS scores, possibly explained by suggestion or attribution effects rather than pharmacological differences. Disclosure of Interest: None declared